2015
DOI: 10.3352/jeehp.2015.12.12
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the qualitative: making sense of written comments from an evaluative satisfaction survey

Abstract: Purpose:Satisfaction surveys are common in the field of health education, as a means of assisting organizations to improve the appropriateness of training materials and the effectiveness of facilitation-presentation. Data can be qualitative of which analysis often become specialized. This technical article aims to reveal whether qualitative survey results can be visualized by presenting them as a Word Cloud.Methods:Qualitative materials in the form of written comments on an agency-specific satisfaction survey … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 11 publications
0
27
0
7
Order By: Relevance
“…It is an ethnically diverse region with a population of 52 million, and more than 70% of the population are living in rural areas [15]. China’s rural health system is organised around three tiers.…”
Section: Methodsmentioning
confidence: 99%
“…It is an ethnically diverse region with a population of 52 million, and more than 70% of the population are living in rural areas [15]. China’s rural health system is organised around three tiers.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, knowledge of healthcare students about the local regulatory body and local reporting system of ADR reporting was inadequate. One study conducted by Khan et al compared the knowledge between medical and pharmacy students and found that pharmacy students have a significantly higher knowledge of pharmacovigilance compared to medical students [26]. Another study by Sivadasan et al had also compared medical to pharmacy students and found that pharmacy students have better knowledge and perception towards pharmacovigilance and ADR reporting compared to medical students [12].…”
Section: Pharmacovigilance Knowledgementioning
confidence: 99%
“…Attitude towards pharmacovigilance and ADR reporting was measured using multiple-choice response options ranging from 2 to 5 questions [20,30], and using a 5-point Likert scale [16,24]. Although only a few studies evaluated attitude; it should be noted that some questions used were related to measuring the perception rather than attitude [16,22,26,31]. The most commonly asked question was about the willingness of students to report any ADR in their future practice (S3 Appendix).…”
Section: Pharmacovigilance Attitudementioning
confidence: 99%
“…Faculty responses were constructed into a Word Cloud to illustrate key words across participants' responses. In a narrative framework, repetition emphasizes and can signal patterns and relationships between, as well as divergences between, individual participant's perceptions of their experiences (Bletzer, 2015). Word clouds have been used in survey research to communicate the relationship between mathematical proportions and a holistic perception (Ahearn, 2014;Bletzer, 2015).…”
Section: List 10 Wordsmentioning
confidence: 99%
“…In a narrative framework, repetition emphasizes and can signal patterns and relationships between, as well as divergences between, individual participant's perceptions of their experiences (Bletzer, 2015). Word clouds have been used in survey research to communicate the relationship between mathematical proportions and a holistic perception (Ahearn, 2014;Bletzer, 2015). Participants' lived experiences were communicated in words, quantified by the researchers, and then qualitatively displayed as a means of representing the essence of the phenomenon (Giorgi, 2009).…”
Section: List 10 Wordsmentioning
confidence: 99%